Estudo experimental do fenômeno da ebulição em um termossifão de vidro - Souza, Diógenes Oliveira de (2019)
Thermosiphons are devices used to exchange heat and are more efficient than conventional heat exchangers. For the correct dimensioning of the thermosiphons, specific correlations are required for the boiling process that occurs in the evaporator. There are several studies related to obtaining correlations to estimate the boiling heat transfer coefficient, however there is a marked divergence between them; especially with regard to the boiling regimes: nucleated and liquid film. These boiling regimes are related to the heat flow applied to the evaporator and the filling ratio (in relation to the evaporator volume). Therefore, in this work, the boiling regimes in the evaporator of a glass thermosiphon are studied, with water as the working fluid, for a filling ratio of 100%, varying the heat transfer rate applied to the evaporator from 110 to 150 W. For this study, an experimental set up was designed and built at NUEM / UTFPR to test the thermosiphon, which was instrumented with temperature sensors, pressure transducers and two resistive mesh sensors (Wire-mesh sensor). The experimental data obtained were used to estimate the boiling heat transfer coefficient both by correlations in the literature and by mass and energy balance. It was observed, even with the slug flow, that for low powers the nucleated boiling regime predominated throughout the evaporator (the average experimental coefficient varied from 1,188 W/m2K to 3,582 W/m2K). On the other hand, for the higher powers (130, 140 and 150 W) the nucleated boiling regime was observed at the lower end of the evaporator (ranged from 2,108 W/m2K to 4,417 W/m2K) and at the upper end the liquid film boiling regime (ranged from 8,566 W/m2K to 18,357 W/m2K). The comparison between experimental and theoretical results showed that the existing correlations do not include these two regions (nucleated and liquid film boiling) observed in this work for the same power. The results obtained directly or indirectly through the wire-mesh sensors are extremely important in determining the parameters related to the flow of bubbles, such as: frequency, translational velocity, void fraction and length of the liquid column (slug). It was observed that the velocity of the bubble was inversely proportional to the applied power and that the volume of liquid (slug) displaced by the rise of the elongated bubble was proportional to the power.